Implementasi Algoritma Backpropagation Dalam Memprediksi Jumlah Penduduk Usia Produktif Pada Kota Pematangsiantar - Mhd Ridho Azhar; Sumarno Sumarno; Indra Gunawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The productive age itself is a population in the age group between 15 to 64 years, whether they work, go to school, and take care of the household, in this case individuals who are in the scope of productive age are people who can still work well to produce a product and services. This study uses an Artificial Neural Network (ANN) with the backpropgation method. The backpropagation algorithm is one of the existing methods of neural networks as a prediction, estimation, classification, and pattern recognition algorithm. The research data is secondary data sourced from the Central Statistics Agency (BPS) from 2013 to 2015. The data is divided into 2 parts, namely training and testing data. There are 5 architectural models used in this study. 2-20-1, 2-21-1, 2-22-1, 2-23-1, 2-24-1. Of the 5 architectural models used, the best 1 model is obtained, namely 2-24-1 with an accuracy level of 80%, MSE 0.00085177 and epoch 100. So this model is good for predicting the number of productive age population in the city of Pematangsiantar in the future